The Influence Of Leverage, Corporate Governance And Capital Intensity On Tax Avoidance In Mining Companies Listed On The Indonesia Stock Exchange Year 2020 – 2023 - Simanjuntak, Gracesiela Yosephine; Simanjuntak, Arthur; Sagala, Farida; Ginting, Mitha Christina; Sagala, Lamria (Program Studi Akuntansi Universitas Simalungun, 2024)
This research aims to examine the influence of leverage, corporate governance and capital intensity on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2020-2023. Samples were taken using the purposive sampling method. The population in this research is all mining companies listed on the Indonesia Stock Exchange in 2020-2023. From this population of 43 mining companies, 9 mining companies were obtained as samples. Data were analyzed using multiple linear regression. The test results show that the variable profitability, leverage has a positive effect on tax avoidance. The board of commissioners and the audit committee as proxies of corporate governance as well as the capital intensity variable also show a positive influence on tax avoidance